Pendampingan Pembelajaran Kosakata Bahasa Inggris melalui Strategi Interaktif bagi Anak di Balai Pengajian Aceh Utara - Hayatul Muna; Ainol Mardhiah; Rusma Setiyana; Erlidawati Erlidawati (Nawadeepa: Jurnal Pengabdian Masyarakat, 2026)
In the era of knowledge and technological advancement, language acquisition has become one of key indicators of educational success, yet opportunities to learn English remain limited in many non-formal educational settings, particularly in rural areas. This program was designed to introduce basic English vocabulary through interactive and meaningful learning experiences for students at several Qur'anic Learning centers (TPQ) in North Aceh, including Balai Pengajian Darul Yaqin, Meunasah Samakurok, Dayah Tahzibuddin, dan Zauhar Malikussaleh. This program aimed to improve young learner ability to recognize, pronounce, memorize and use basic vocabulary in daily activities through enjoyable and meaningful experiences. The activities were conducted to 45 young learners with the age range 6-12 years. Integrating service learning with the teaching for young learner courses, these activities were implemented through five stages: investigation, planning, action, reflection, and presentation. Various interactive media and teaching strategies were implemented, such as Total Physical Response (TPR), educational games, flashcards, role play, and song. The result indicated that students showed high enthusiasm and active involvement during the activities. The students were able to recognize and memorize basic English vocabularies related to fruits, colors, parts of body, transportation, family members, and animals. The use of contextual media strengthened students’ understanding of English vocabulary acquisition. Finally, this program is expected to become a sustainable education model to promote English for young learners in rural community.